ANALISIS MANAJEMEN PELAKSANAAN PADA KESIAPSIAGAAN DAN TANGGAP DARURAT DI GEDUNG PERKANTORAN X - Maulana Said Handayana; Suroto Suroto; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Office building X has an area of 52 753 m2 with a height of 120 m. As a multi-storey building, of course, office building X has a wide range of risk emergencies. This study aims to analyze the management of implementation on preparedness and emergency response in the office building X. This research is a descriptive qualitative in-depth interviews. The subject of this research consists of 5 person as the main informants and 3 person as the informant triangulation. The results showed that the management of office buildings X already have policies and commitments in terms of preparedness and emergency response. This is indicated by the emergency response procedures, the top management support such as funding and systemic policy, the emergency response organizations, the emergency communications, the emergency response infrastructure, the transportation of emergency response, the emergency response training, the emergency response simulation and evaluation of emergency response procedures. But the management of office buildings X doesn’t have a program for hazard identification and risk assessment, the emergency response procedures is not contain of information about protection facilities and equipment available as well as the duties and responsibilities of emergency response organizations, there are tenants which has not obtain information related to emergency response procedures, procedure has not been set for the recovery of labor conditions or facilities that were damaged, the top management has not actively participate in simulated emergencies, emergency response organization is not consist of building occupants and building managers, unavailability of backup emergency vehicles, unavailability of stretcher and evacuation chair, assembly point which can not accommodate all the building occupants, the recapitulation process of building occupants were evacuated when simulating emergencies requires a long time. The management of office buildings X should complement existing emergency response procedures as well as reviewing other supporting facilities such as the support of top management, emergency response organizations, emergency response infrastructure, emergency response transportation and emergency response training.